Cognitive Development and Reflective Judgment in Information Literacy - Michael Fosmire (Issues in Science and Technology Librarianship)
The article introduces the column "What I've Been Reading" to be featured in "Issues in Science and Technology Librarianship" which aimed to provide a venue for encouraging librarianship research into practice.